Taxonomic revision of genus Loxoconcha in Japan and Vietnam and its origin - Le, Doan Dung (Vietnam Journal of Marine Science and Technology, 2025)
In preceding the study, 30 species of the genus Loxoconcha, which were collected on reef slopes, reef flats, tidal beaches, and river mouths in Japan and Vietnam from 2012 to 2015, are reviewed taxonomically. Based on carapace characteristics, such as hinge, fulcral point, muscle scars, and frontal scars, the results show that 27 species still prove to be the genus Loxoconcha. However, two species are assigned to Bonnyannella and one to Sagmatocythere and re-described. In addition, this research also initially reveals the origin and distribution in the Atlantic Ocean of the genus Loxoconcha which is considered as one of the most diversified recent genera in marine ostracods. Fossil records of Loxoconcha species worldwide show that the origination of the genus Loxoconcha may be in Indo-West Pacific Region and by the Late Oligocene (possibly the Late Eocene). To this day, most fossil records of the genus Loxoconcha belong to group A. Among the three subgroups of group A, species subgroup A1 is distributed widely in Indo-West Pacific Region, and therefore, subgroup A1 may be an origin group of the genus Loxoconcha. The geographical distribution of subgroups A2 and A3 mainly restricted within European marine water, including the Mediterranean Sea, meanwhile subgroup A1 lives around the World except for the distributional areas of subgroups A2 and A3, suggesting that the Atlantic Ocean may be a barrier to dispersing subgroups A1 and A2 (and A3).